Comportamiento agronómico de plántulas de cacao (theobroma cacao L.), en vivero, sembradas en diferentes volúmenes de sustrato. Quevedo - Macías Zambrano, José Walter (2013)
The research was conducted in the Canton Quevedo, Ecuador Los Ríos Province, is among the geographical coordinates 79 ° 25 '24 "west longitude and 01 ° 02'18" south latitude at an altitude of 170 m research lasted 180 days. a) evaluate the agronomic performance of seedlings CCN-51 cacao (Theobroma cacao L.) in nursery, planted in different volumes of substrates, b) Determine the length of the taproot in cocoa nursery stage CCN-51en different volumes substrate, c) Establish the best volume of substrates in the nursery for the propagation of plants grafted cacao CCN-51. d) Determine the costs for treatment studies. The experimental unit consisted of 50 plants were a total of 300 for treatment and patterns 1500 was used cacao variety CCN-51, with different volumes of substrate. The treatments used were T1 = Case (5x7), T2 = Case (5x8), T3 = Case (6x10), T4 = Case (7x11), T5 = Case (8x10). Was used Completely Randomized Design (DCA) with five treatments and six replications was established difference between treatment means using the multiple range test of Tukey at 95% probability. The variables to be measured, germination percentage, diameter of stem, plant height, number of leaves, leaf width, llongitud leaves, root length, in enjertación stage following variables were evaluated, survival (%), shoot height, leaf length, thick buds, leaf width, economic analysis........................